Strategies for Dam Safety Risk Management in Mexico - Botero Jaramillo, Eduardo; Ossa López, Alexandra; Flores Berrones, Raúl (Tecnología y ciencias del agua, 2015)
Safety protocols for dams worldwide are currently based mainly on: understanding possible failures; quantitative risk assessment; justification of risks taken (with reference to accepted standards and good practices); historical records of dam performance; new criteria and state-of-the art designs; the need to prioritize research; solutions to known problems; better communication of risks to the public, civil organizations and decision- makers; and the improvement of risk management through clearly defining and assigning responsibilities (Bowles, 2013). In addition, these protocols are equally applied to dam owners, regulatory organizations, insurance companies and consulting companies. This article discusses the current framework used to evaluate dam safety at the international level and proposes a specific methodology to evaluate existing dams in Mexico. It also discusses the urgent need to study the possibility of removing dams that present unacceptable risks and for which rehabilitation is not cost-effective.